Ettore Sottsass - Ceramics - Sottsass, Ettore; Bischofberger, Bruno (Zürich : Stemmle, 1995)
Focus op de keramiek van Sottsass, zowel decoratief als functioneel
Engels
boek
Keywords: Sottsass, Ettore; 1956 - 1995; Italië